Corporitual - "Bhowmik, Raj" (Delhi, 2008)
Corporitual indicates a way of living that creates a harmonious balance between the fast-paced corporate life and our serene spiritual life. According to Raj Bhowmik this is the only formula for peace and tranquility in today$1 (Bs fast-paced life. In this book Raj creates a magical ambience to discuss the most important Corporitual values essential for a higher living. A Corporitual life will help you to afford and enjoy all the comforts and luxuries of life and at the same time, a serene and divine energy inside you will fill you to your hearts content, enabling you to make better choices in your daily living. The best thing about accepting and following the values is that it will not only help you experience life transforming changes within yourself to give you the winner's position and success that you are looking for, but will also help you to make a huge difference to the society as a whole and also to everyone's life who are around you.s
Keywords: Corporate life